Drone Assisted Robust Emergency Service Management for Elderly Chronic Disease - Jiang, Shengqiang; Jin, Yong; Xia, Kaijian (Journal of healthcare engineering, 2021)
It is important to monitor the early screening of chronic diseases, predict the risk, and provide the comprehensive management of chronic diseases for the elderly. However, it is difficult to provide the robust and real-time emergency service for elderly chronic disease because of the complex social network and diversity of elderly chronic disease service. To address these issues, we design a new drone assisted robust emergency service system. We formulate the Drone assisted Management (DM) problem to minimize the total time cost of drone subject to all elderly chronic disease services which can be guaranteed exactly once by the drone under its energy constraint. Then, we propose the DRS algorithm to solve the DM problem. To provide the robust and real-time service, we further formulate the Charging driven Drone assisted Management (CDM) problem and present the CDRS algorithm to solve the CDM problem. Through the theoretical analysis and numerical simulation experiments, we demonstrate that DRS and CDRS can decrease the total time cost by 37.61% and increase the QoE by 112.80% through the designed system, respectively.